Civilizations at Odds: The Persistent Conflict Between Israel and Palestine - Maria Mansab (National University of Modern Languages (NUML), Islamabad, 2024)
The question whether the issues in the Middle East stem from a clash of values or from Western imperialist intervention has long been a subject of scholarly discourse. This article posits around the discourse of 'clash of civilizations', which is an endeavor to uphold Western hegemony in the Middle East. Furthermore, it contends the narrative, that it functions as a self-fulfilling prophecy, exacerbating ongoing conflicts within the region. A complex interplay of factors encompassing ethnic, national, historical, and religious shapes the Israeli-Palestinian conflict. The degree to which religion influences non-religious players, the identities of conflicting parties, the practical issues at hand, the relevant legislation, and their attitudes are not well acknowledged. This paper explains why West uses a distorted portrayal of conflicting civilizations as a powerful political tool and the risk of this narrative becoming a self-fulfilling prophecy that reshapes modern politics.